(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Hospital acquired infections are still a health care problem across many countries. However, the implementation of the requiredand recommended infection control practices is unsatisfactory. Methods: This was a 6-month cross-sectional study in five regions’ privatehospitals in Saudi Arabia. Results: All the hospitals’ infection control practices were below 75%. Administrators, doctors, nurses, and alliedmedical staff’s were of practicing infection control varied across the five hospitals. Only the doctors and allied medical staff responded withmore “yes” than “no” to infection control practice questions. Conclusion: The infection control program and practices in private hospitals inSaudi Arabia are still demanding. Unless these practices are improved across private-sector hospitals, the prevalence and burden of hospitalacquired infections will remain in place.